Sexual orientation and gender identity disparities in substance use disorders during young adulthood in a united states longitudinal cohort - Jun, Hee-Jin (Drug Alcohol Depend, 2019)
BACKGROUND: This study examined associations of sexual orientation and gender identity with prevalence of substance use disorders (SUDs) and co-occurring multiple SUDs in the past 12-month during young adulthood in a United States longitudinal cohort. METHODS: Questionnaires self-administered in 2010 and 2015 assessed probable past 12-month nicotine dependence, alcohol abuse and dependence, and drug abuse and dependence among 12,428 participants of an ongoing cohort study when they were ages 20–35 years. Binary or multinomial logistic regressions using generalized estimating equations were used to estimate differences by sexual orientation and gender identity in the odds of SUDs and multiple SUDs, stratified by sex assigned at birth. RESULTS: Compared with completely heterosexuals (CH), sexual minority (SM; i.e., mostly heterosexual, bisexual, lesbian/gay) participants were generally more likely to have a SUD, including multiple SUDs. Among participants assigned female at birth, adjusted odds ratios (AORs) for SUDs comparing SMs to CH ranged from 1.61–6.97 (ps<.05); among participants assigned male at birth, AORs ranged from 1.30–3.08, and were statistically significant for 62% of the estimates. Apart from elevated alcohol dependence among gender minority participants assigned male at birth compared with cisgender males (AOR: 2.30; p<.05), gender identity was not associated with prevalence of SUDs. CONCLUSIONS: Sexual and gender minority (SGM) young adults disproportionately evidence SUD, as well as co-occurring multiple SUDs. Findings related to gender identity and bisexuals assigned male at birth should be interpreted with caution due to small sample sizes. SUD prevention and treatment efforts should focus on SGM young adults.